Bioecological and physiological-biochemical features of cassocks (Lemnaceae) in culture (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents the result of the study of three species of duckweed: duckweed (Lemna minor L.), duckweed (Lemna gibba L.) and duckweed (Lemna trisulca L.). The subject of the study is inthe pouring of various nutrient media on the growth and development of duckweed in culture. It should be emphasized that the treatment of polluted water in biological ponds with the use of hydromacrophytes is effective and not time-consuming. This method of cleaning polluted effluents can be especially promising in the conditions of the Republic, because the duration of the warm period is 210-215 days.